Animal Studies and Ancient Judaism. (October 2019) - Berkowitz, Beth
Animal studies has its origins in philosophy but extends to all fields of the humanities, especially literature, history, and anthropology. The central concern of animal studies is how human beings perceive other species and themselves as one among them. Animal studies in ancient Judaism has generally not been undertaken in a critical mode, with notable and increasing exceptions. This article covers work from the past decade (2009–2019) that deals centrally with animals, from ancient Israel to late antiquity, spanning the Hebrew Bible, apocrypha and pseudepigrapha, library of Qumran, rabbinic literature, and material culture. Topics addressed are animal sacrifice and consumption; literary depictions of animals; studies of individual animal species; archaeology and art featuring animals; animal ethics, theology, and law; and critical theoretical approaches to species difference. The conclusion considers future directions for animal studies in ancient Judaism.